EFEKTIVITAS PELAKSANAAN SUPERVISI KEPALA BADAN TERHADAP KINERJA PEGAWAI PADA BADAN PENELITIAN PENGEMBANGAN DAN PERENCANAAN (BALITBANGREN) KABUPATEN POLEWALI MANDAR - Mukhlis Hannan; Moch. Arfandi Adnan; Marsuki Marsuki (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to determine the effect of the implementation of the effectiveness of the Head of the Agency's supervision of the Employee Performance of the Research Development and Planning Agency of Polewali Mandar Regency. This research uses quantitative, and data collection techniques through a respondent approach by distributing questions about the variables of effectiveness, supervision, and performance. The results obtained from the development of supervision can be carried out effectively with the effectiveness of 50.6 while supervision is 48.8 and performance is 50.4. Developing performance by prioritizing maximum supervision can provide optimal results in improving the quality of employee performance. Overall, the implementation of supervision in the research agency for development and planning of Polewali Mandar Regency runs effectively.